When Art Becomes a Rectification of Humankind: Gary and Malraux, A Same Aesthetic Humanism? - Mourlan, Lou (Literatūra, 2022)
When we question the humanism of Gary or Malraux, we see the question of art arise on all sides. Aesthetics and ethics indeed seem intrinsically linked, firstly because, for them, art is a way of denying the inhuman, whether it be the absurdity of our condition or the crushing weight of History. At a time when the Second World War brought human barbarism to the forefront, what the artist gave us in his works was a finally acceptable image of humankind. Art, according to them, is, at the same time, a consolation and a shelter for humanist ideals, and an ethical gesture in itself. We will try here to confront in Gary’s and Malraux’s books the connections between art and humanism, and to question the existence in these two authors - while preserving the specificities of each - of what one could call an aesthetic humanism.
Keywords: humanism; aesthetics; ethic; art; Word War II; novel; myth